LACTASE DEFICIENCY IN EARLY CHILDHOOD AND DIETARY THERAPY - Feruza Asqarova, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: Lactase deficiency represents one of the most prevalent functional gastrointestinal disorders in infants and young children. This condition arises from insufficient activity of the lactase enzyme in the small intestine, leading to incomplete digestion of lactose. Consequently, undigested lactose undergoes bacterial fermentation, producing symptoms such as abdominal distension, flatulence, diarrhea, irritability, and inadequate weight gain. These manifestations can negatively impact nutritional status and overall physical development.Lactase deficiency can be categorized into primary (genetic) and secondary forms. Primary deficiency is generally inherited, while secondary deficiency develops due to intestinal infections, inflammatory conditions, allergic reactions, or dysbiosis. Early identification of affected children is essential to prevent growth retardation and associated complications.Dietary management is the cornerstone of treatment. For formula-fed infants, low-lactose or lactose-free formulas effectively reduce lactose load while ensuring essential nutrients are provided. In breastfed infants, continuation of breastfeeding combined with oral lactase enzyme supplementation maintains optimal nutrition. Individualized dietary strategies restore intestinal mucosal function, alleviate symptoms, and promote healthy growth.In conclusion, lactase deficiency in early childhood demands timely diagnosis and tailored dietary therapy. Adherence to personalized management protocols ensures symptom relief, proper nutritional intake, and supports normal physical development, thereby improving quality of life and long-term outcomes for affected children.